Bengkulu Coffee Production Development - Anzori Tawakal; Ricky Zulfiandry; Eko Sumartono; Silke Sachanovrissa; Evi Andriani (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
As an agricultural community, in general, Bengkulu province has gardening. The largest plantations for the community are oil palm, rubber and coffee commodities. People depend their lives on abundant natural potentials but have not been able to manage them properly to stimulate added value. All potentials are still managed traditionally so that productivity is very low. The province of Bengkulu is the 3rd largest national coffee producer, but so far Bengkulu coffee is sold through Lampung and Palembang so it is not known outside. The problems are: The low income and welfare of the coffee farmers in Bengkulu province; The promotion and branding of Bengkulu coffee has not been recognized either nationally or internationally. The intention of compiling the Bengkulu coffee development master plan. One of the activities carried out is conducting research or mapping potential and mapping policy directions in the field of coffee development in Bengkulu Province. The aim of compiling the Bengkulu coffee development master plan a) Increasing the income of coffee farmers in Bengkulu province, b) Increasing the promotion and branding of Bengkulu Coffee at the national and international levels c) Increasing the knowledge of farmers and field officers towards coffee cultivation technology farmers: d) Increasing the role and function of farmer institutions in plantation areas coffee; e) Preparing technological innovations to increase coffee production and quality; The scope of activities is focused on coffee development in the Bengkulu area from upstream, production, downstream and provincial, district / city governments as well as Stake Holders / stakeholders.